Answers:
14 + 18 ÷ 2 x 18 – 7 = 169
- 14 + 9 * 18 - 7
- 14 + 162 - 7
- 169
60 – 9 x 8 ÷ 8 x 6 = 6
- 60 - 72 / 8 * 6
- 60 + -216/4
- 60 - 54
- 6
15 x 10 + 12 ÷ 3 + 9 = 163
- 150 + 12 / 3 + 9
- 150 + 4 + 9
- 163
(10 ÷ 5)3 + 100 – 9 x 11 = 7
- 2 * 3 + 100 - 9 * 11
- 6 + 100 - 99
- 7
8 x 4 + 9 – 9 + 18 = 50
- 32 + 9 - 9 + 18
- 41 - 9 + 18
- 32 + 18
- 50
3 x 8 x 2 – 42 + 5 = 11
- 24 * 2 - 42 + 5
- 48 - 42 + 5
- 11
<em>i hope this helps, good luck :)</em>
63 because both angles are the same
3
2
+
3
−
7
Distribute
(
6
2
−
4
−
5
)
−
1
(
3
2
−
7
+
2
)
(
6
x
2
−
4
x
−
5
)
−
1
(
3
x
2
−
7
x
+
2
)
(6x2−4x−5)−1(3x2−7x+2)
(
6
2
−
4
−
5
)
−
3
2
+
7
−
2
Answer:
y = 7
Step-by-step explanation:
5(3y - 13) = 6y - 2
5*3y + 5*-13 = 6y - 2
15y - 65 = 6y - 2
15y - 6y = 65 - 2
9y = 63
y = 63/9
y = 7
Check:
5((3*7)-13) = 6*7 - 2
5(21-13) = 42 - 2
5*8 = 40
2 consecutive odd integers...x and x + 2
x + (x + 2) = 36
2x + 2 = 36 <===